ANALISIS KUALITAS HASIL REPAIR WELDING TERHADAP SIFAT FISIS DAN MEKANIS PADA CAST WHEEL ALUMINIUM DENGAN METODE PENGELASAN OKSI-ASETILIN - Chafiedz, Nur (Jurnal Nosel, 2013)
The purposes of this research are: (1) To know microstructure oxy- acetylene welded joints in aluminium cast wheel.,(2) To know hardness aluminium cast wheel before and after oxy-acetylene welding.,(3) To know the impact strength in aluminium cast wheel before and after oxy-acetylene welding From the research, we can conclude that the chemical composition on aluminium cast wheel including alloy Aluminium Silicon, because the element Si alloy is the largest, ie 7.38% Si. Microstructure on base metal granules the spread equally on the surface of Al. Specimen hardness value raw material higher than oxy-acetylene welding specimens. The average value of raw material hardness results 57.58 BHN while the average value of oxy-acetylene welding results 54.80 BHN. Average hardness oxy-acetylene welding specimens in the HAZ area 38.69 BHN. The average value of raw material impact results 0,12 J/mm² while the average value of oxy-acetylene welding results 0,085 J/mm².